2013
DOI: 10.1158/1535-7163.mct-12-1249
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Small Molecules Targeting the Vitronectin-Binding Site of the Urokinase Receptor That Block Cancer Cell Invasion

Abstract: Besides focusing urokinase (uPA) proteolytic activity on the cell membrane, the uPA receptor (uPAR) is able to bind vitronectin, via a direct binding site. Furthermore, uPAR interacts with other cell surface receptors, such as integrins, receptor tyrosine kinases, and chemotaxis receptors, triggering cell-signaling pathways that promote tumor progression. The ability of uPAR to coordinate binding and degradation of extracellular matrix (ECM) and cell signaling makes it an attractive therapeutic target in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…In some cases, circulating uPAR DI shed by proteolysis is an even more powerful prognostic biomarker than intact uPAR [47,48]. Inline with these properties, uPAR is considered a relevant translational target for intervention therapy and huge efforts have accordingly been allocated, in recent years, to development and preclinical testing of various uPAR targeting strategies including uPA-activated prodrugs [49], small-molecule inhibitors [12,31,50], targeted radiotherapy [51], and mAbs [52,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, circulating uPAR DI shed by proteolysis is an even more powerful prognostic biomarker than intact uPAR [47,48]. Inline with these properties, uPAR is considered a relevant translational target for intervention therapy and huge efforts have accordingly been allocated, in recent years, to development and preclinical testing of various uPAR targeting strategies including uPA-activated prodrugs [49], small-molecule inhibitors [12,31,50], targeted radiotherapy [51], and mAbs [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this flexibility has to be taken into account if molecular modeling is used for drug discovery and refinement of small-molecule antagonists targeting these two known uPAR·ligand interfaces [12,23,30,31], as well as when docking simulations are used to build model structures of hitherto unsolved uPAR·ligand complexes [32].…”
Section: Introductionmentioning
confidence: 99%
“…A possibility is to interfere with uPAR/FPRs interaction. Recently, Rea and co-workers described small molecules that impaired cell migration in virtue of their ability to target the Ser 88 and Arg 91 residues of uPAR and, consequently, uPAR/FPR interaction [48]. In this context, RERF peptide which, able to interfere with the invasive phenotype of ovarian cancer cells by inhibiting uPAR 84-95 -triggered, FPR-mediated signals, could be considered a valid prototype for the development of new anti-neoplastic therapies designed to simultaneously counteract growth and abdominal dissemination of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chiron Corporation screened a phage-display library to identify uPAR antagonists 105 , but no further studies were reported on the antitumor effects of these peptides. Small molecules that interrupted the interaction between uPAR and vitronectin inhibited the invasion of cancer cells in vitro 106 . The Meroueh group synthesized a series of pyrrolidinone and piperidinone derivatives that bind to the uPA-binding pocket of uPAR 107 .…”
Section: Upar Antagonists As Anticancer or Anti-inflammatory Agentsmentioning
confidence: 98%